Cost-effective usage of membrane oxygenators in extracorporeal membrane oxygenation in infants. (April 2015) - Özyüksel, A; Ersoy, C; Akçevin, A; Türkoğlu, H; Çiçek, AE; Kahraman, A; Kayhan, B; Cantürk, E
Although the poly-methylpentene (PMP) oxygenators have significant advantages in ECMO implementation, their usage may be limited in some situations, which may be related to economic constraints. In this report, we aimed to emphasize our cost-effective usage of a membrane oxygenator at the ECMO setup. We implemented ECMO with eight Capiox ® FX05 or Baby RX05 hollow-fiber membrane oxygenators in five neonatal patients. The average ECMO duration was 121 hours (ranging from 41 to 272 hours). Following the termination of the ECMO, the system was broken down into its components for macroscopic analysis. Neither gross blood clots nor plasma leakage were observed in any of the components. The integration of a centrifugal pump and a separate hollow-fiber oxygenator may provide a cost-effective ECMO implementation setup with no adverse effects which may be an encouraging alternative for the low cost usage of ECMO in neonates.